Engagement of the Cellular Receptor for Glycoprotein B of Human Cytomegalovirus Activates the Interferon-Responsive Pathway - Boyle, Kathleen A. (American Society for Microbiology, 1999)
Cells respond to contact with human cytomegalovirus (HCMV) virions by initiating intracellular signaling and gene expression characteristic of the interferon (IFN)-responsive pathway. Herein, we demonstrate that a principal mechanism of HCMV-induced signal transduction is via an interaction of the primary viral ligand, glycoprotein B (gB), with its cellular receptor. Cells incubated with a purified, soluble form of gB resulted in the transcriptional upregulation of IFN-responsive genes OAS and ISG54 (encoding 2′-5′ oligoadenylate synthetase and an IFN-stimulated gene product of 54 kDa) to a comparable level as virions or IFN. Gene induction was an immediate and direct response to gB which did not require de novo protein synthesis. Neither the initial virus attachment site, heparan sulfate proteoglycans, nor the IFN-α/β or IFN-γ receptors are involved in the response. Pleotropic protein phosphorylation was required for cellular gene induction, and the mitogen-activated protein kinases ERK1 and ERK2 were activated in response to the ligand. Together these data indicate that a principal means by which cytomegalovirus induces intracellular signaling and activation of the interferon-responsive pathway is via an interaction of gB with an as yet unidentified, likely novel cellular receptor that interfaces with the IFN signaling pathway.